FAKTOR-FAKTOR YANG MEMPENGARUHI PENGGUNA APLIKASI GOPAY DI JAKARTA - Nabila Adilah Rohmah; Heny Kurnianingsih (CV. Adiba Aisha Amira, 2023)
This research aims to find out, analyze and explain whether age, gender and lifestyle factors influence a person's interest in using Gopay. As well as to find out, analyze and explain which factors have a dominant influence on someone's interest in using Gopay. The research method used is descriptive quantitative with data collection techniques using questionnaires. The population in this research is the people of Jakarta who have an interest in using Gopay with a sample of 97 respondents, using a non-probability sampling technique determined by purposive sampling, namely a technique for determining samples with certain considerations. Based on the research results, it shows that the total explained results show the age factor with a total variance of (28.1%), gender factor (29.4%) and lifestyle factor (37.5%). The dominant factor that most influences people's interest in using the Gopay application in Jakarta is the lifestyle factor with a total variance value of 37.5%.. The research results show that age, gender and lifestyle have a significant influence on interest in using GoPay.